1999
DOI: 10.1148/radiology.211.3.r99jn19623
|View full text |Cite
|
Sign up to set email alerts
|

Renal Volume Measurements: Accuracy and Repeatability of US Compared with That of MR Imaging

Abstract: Use of US with the ellipsoid formula is not appropriate for accurate and reproducible calculation of renal volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
200
6
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(224 citation statements)
references
References 32 publications
15
200
6
3
Order By: Relevance
“…18 However, previous studies have shown that renal volume calculations obtained by the ellipsoid formula in healthy volunteers resulted in a 25% underestimation of renal volumes compared with those obtained by a voxel count magnetic resonance imagingbased method. 6,7 In this study, the ellipsoid formula resulted in a 15.7% underestimation of renal volumes, which was less than that reported previously. 6,7 A few studies have concluded that renal volume measurements obtained by 3D sonography are accurate and correlate well with reference standard methods.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…18 However, previous studies have shown that renal volume calculations obtained by the ellipsoid formula in healthy volunteers resulted in a 25% underestimation of renal volumes compared with those obtained by a voxel count magnetic resonance imagingbased method. 6,7 In this study, the ellipsoid formula resulted in a 15.7% underestimation of renal volumes, which was less than that reported previously. 6,7 A few studies have concluded that renal volume measurements obtained by 3D sonography are accurate and correlate well with reference standard methods.…”
Section: Discussioncontrasting
confidence: 78%
“…6,7,10,19 In this study, our preliminary study of cadaveric pig kidney volumes measured by the voxel count method with CT data were almost identical to those obtained by the water displacement method. Furthermore, Figure 7.…”
Section: Discussionsupporting
confidence: 70%
“…Given its poor precision (5), this measurement should be performed several times. Since the poor precision stems mostly from undermeasurement, the maximum length is the value that should be reported.…”
Section: Size and Shapementioning
confidence: 99%
“…Measurement of other dimensions is even more imprecise and is of no utility. The same applies to the estimation of kidney volume, which correlates poorly with more accurate techniques (5). Kidney length in adults should usually be between 10-12 cm but varies with body size and, unfortunately, there are no nomograms for normal kidneys based on large population studies.…”
Section: Size and Shapementioning
confidence: 99%
“…A number of investigators have reported reference values for renal length (7)(8)(9)(10)(11)(12) and, to a lesser extent, renal volume in healthy adults (7,8), as measured by ultrasonography. The ultrasonography method that is used to measure kidney volumes is two-dimensional in nature, is subject to operator dependence, and uses geometric assumptions about the shape of the kidney to estimate kidney volumes.…”
mentioning
confidence: 99%